DETERMINATION OF TAXPAYER (WP) COMPLIANCE WITH MOTOR VEHICLE TAX (PKB) IN SAMSAT MEDAN AND INFLUENCE FACTORS - Meidiaz, Emily Vanessa; Subagyo (Universitas Airlangga, 2023)
This research aims to find out whether service quality, perceived income level, tax sanctions and tax relief have an effect on motor vehicle taxpayer compliance at SAMSAT Medan. This research uses primary data by distributing questionnaires to motor vehicle taxpayers at SAMSAT Medan. The number of respondents who were sampled and completely filled out the research questionnaire was 194 respondents. The research model uses multiple linear regression analysis with data processing using SPSS. The results of the research show that service quality and tax sanctions have a significant positive effect on taxpayer compliance (WP) with motor vehicle tax (PKB) at SAMSAT Medan, while perceptions of income level and tax relief do not have a significant positive effect on taxpayer compliance (WP) with motor vehicle tax ( PKB) at SAMSAT Medan. In developing knowledge, especially in the field of taxation, with this research, it will be a concern for study program managers to add portions of material related to taxation, especially regional taxes. Taxpayers are expected to provide information and input regarding the importance of motor vehicle owners paying motor vehicle tax on time. It is hoped that the Medan SAMSAT Office can provide input as a solution in order to improve and increase motor vehicle taxes in order to increase regional income. The limitations of this research are that there are still taxpayers who do not know about the tax whitening policy and there is a lack of information regarding when tax whitening is implemented.